Preparation method of cesium lead halide perovskite nanocrystal

By using the metathesis and coordination reaction of P-AMDL polymer ligand with cesium halide and lead halide, combined with the purification step of n-hexane, a high-phase purity and stability of cesium lead halogen perovskite nanocrystals were prepared, which solved the problem of insufficient phase purity and stability of perovskite nanocrystals in the prior art.

CN119874996AInactive Publication Date: 2025-04-25UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510360598.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the perovskite nanocrystal phase prepared by the ligand-assisted reprecipitation method has low purity and poor stability, making it difficult to meet the needs of high purity and high stability.

Method used

P-AMDL polymer ligand was prepared by monomers such as 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylammonium methacrylate and lauryl methacrylate. After mixing with cesium halide and lead halide, metathesis and coordination reaction were carried out, and combined with the purification step of n-hexane, cesium lead halogen perovskite nanocrystals with high phase purity and stability were prepared.

Benefits of technology

The high phase purity and excellent stability of cesium-lead halogen perovskite nanocrystals are achieved, the hydrophobicity and redispersion ability of the nanocrystals are improved, and the structure damage of n-hexane is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874996A_ABST
    Figure CN119874996A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a cesium lead halide perovskite nanocrystal, and belongs to the technical field of nanomaterials. According to the invention, 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate and lauryl methacrylate are used as monomers to prepare a P-AMDL polymer ligand, and a sulfonic acid group, an amide group and an ester group provide a plurality of binding sites for P-AMDL; the long alkyl side chain can be tightly anchored on the surface of the cesium-lead halide perovskite nanocrystal, the hydrophobicity and redispersion capacity of the cesium-lead halide perovskite nanocrystal are improved by the long alkyl side chain, so that the prepared cesium-lead halide perovskite nanocrystal has excellent stability, and normal hexane is adopted for purification, so that the purity of the cesium-lead halide perovskite nanocrystal is improved, and the service life of the cesium-lead halide perovskite nanocrystal is prolonged. And the structure of the cesium lead halide perovskite nanocrystal is not damaged, so that the prepared cesium lead halide perovskite nanocrystal has excellent phase purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to a method for preparing cesium lead halide perovskite nanocrystals. Background Art

[0002] All-inorganic cesium lead halide perovskite has attracted widespread attention as an emerging semiconductor material due to its excellent optical properties, including high fluorescence quantum yield, narrow emission peak and easily adjustable emission spectrum. It can be used in solar cells, light-emitting diodes, photodetectors and other fields. Ligand-assisted reprecipitation (LARP) is a simple room temperature synthesis method suitable for large-scale production of perovskite nanocrystals (NCs). However, the perovskite nanocrystals prepared by this method in the prior art have low phase purity and poor stability. Therefore, how to improve the phase purity and stability of perovskite nanocrystals has become a difficult problem in the prior art. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing cesium lead halide perovskite nanocrystals. The cesium lead halide perovskite nanocrystals prepared by the preparation method provided by the present invention have high phase purity and excellent stability.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing cesium lead halide perovskite nanocrystals, comprising the following steps: (1) 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, a photoinitiator and N,N-dimethylformamide are mixed to carry out a polymerization reaction to obtain a P-AMDL polymer solution; (2) mixing the P-AMDL polymer solution obtained in step (1) with cesium halide and lead halide to obtain a precursor solution; the molar ratio of the cesium halide to the lead halide is 1:2 or 4:1; (3) mixing the precursor solution obtained in step (2) with toluene, performing double decomposition and coordination reaction, and obtaining a crude product; (4) The crude product obtained in step (3) is mixed with n-hexane for precipitation to obtain cesium lead halide perovskite nanocrystals.

[0005] Preferably, in step (1), the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate and lauryl methacrylate is 1: (13-15): (0.5-0.7): (1.6-1.8).

[0006] Preferably, the photoinitiator in step (1) comprises diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide.

[0007] Preferably, in step (1), the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to photoinitiator is 0.5:(0.06-0.07).

[0008] Preferably, in step (1), the volume ratio of the amount of 2-acrylamide-2-methylpropanesulfonic acid to N,N-dimethylformamide is 0.5 mmol: (2-4) mL.

[0009] Preferably, the polymerization reaction in step (1) is carried out under ultraviolet light; the wavelength of the ultraviolet light is 390-400 nm; and the polymerization reaction time is 3.5-4 h.

[0010] Preferably, the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid in step (1) to cesium halide in step (2) is 0.5:(0.1-0.4).

[0011] Preferably, in step (3), the volume ratio of the precursor solution to toluene is 1:(9-11).

[0012] Preferably, the temperature of the metathesis and coordination reaction in step (3) is 20-30° C., and the time of the metathesis and coordination reaction is 10 min-4 h.

[0013] Preferably, in step (4), the volume ratio of the crude product to n-hexane is 1:(0.8-1.2).

[0014] The invention provides a method for preparing cesium lead halide perovskite nanocrystals, comprising the following steps: (1) mixing 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, a photoinitiator and N,N-dimethylformamide, and performing a polymerization reaction to obtain a P-AMDL polymer solution; (2) mixing the P-AMDL polymer solution obtained in the step (1) with cesium halide and lead halide to obtain a precursor solution; the molar ratio of the cesium halide to the lead halide is 1:2 or 4:1; (3) mixing the precursor solution obtained in the step (2) with toluene, and performing a double decomposition and coordination reaction to obtain a crude product; and (4) mixing the crude product obtained in the step (3) with n-hexane, and performing precipitation to obtain cesium lead halide perovskite nanocrystals. The present invention adopts 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate and lauryl methacrylate as monomers to prepare P-AMDL polymer ligand, wherein the sulfonic acid group, amide group and ester group provide multiple binding sites for P-AMDL, which can be tightly anchored in cesium lead halide perovskite (Cs x Pb y X z) nanocrystal surface, and the long alkyl side chain increases the Cs x Pb y X z The hydrophobicity and redispersibility of the nanocrystals make the prepared Cs x Pb y X z The nanocrystals have excellent stability and are purified using n-hexane without causing Cs x Pb y X z The nanocrystal structure is damaged, so that the prepared Cs x Pb y X z The nanocrystals have excellent phase purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is the infrared spectra of AMPS, MMA, DMAEMA, LMA and P-AMDL in Example 1; Figure 2 is the hydrogen nuclear magnetic resonance spectrum of AMPS, MMA, DMAEMA, LMA and P-AMDL in Example 1; Figure 3 XRD patterns of nanocrystals prepared in Examples 1 to 4; Figure 4 The ultraviolet absorption spectra of the nanocrystals prepared in Examples 1 to 4; Figure 5 XRD patterns of nanocrystals prepared in Examples 5 to 8; Figure 6 The ultraviolet absorption spectra of the nanocrystals prepared in Examples 5 to 8; Figure 7 TEM image of the colloidal solution formed after the nanocrystals prepared in Example 1 are dispersed in toluene; Figure 8 TEM image of the colloidal solution formed after the nanocrystals prepared in Example 5 are dispersed in toluene; Fig. 9 This is a test chart of the thermal stability and ultraviolet stability of the nanocrystals prepared in Example 5. DETAILED DESCRIPTION

[0016] The present invention provides a method for preparing cesium lead halide perovskite nanocrystals, comprising the following steps: (1) 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, a photoinitiator and N,N-dimethylformamide are mixed to carry out a polymerization reaction to obtain a P-AMDL polymer solution; (2) mixing the P-AMDL polymer solution obtained in step (1) with cesium halide and lead halide to obtain a precursor solution; the molar ratio of the cesium halide to the lead halide is 1:2 or 4:1; (3) mixing the precursor solution obtained in step (2) with toluene, performing double decomposition and coordination reaction, and obtaining a crude product; (4) The crude product obtained in step (3) is mixed with n-hexane for precipitation to obtain cesium lead halide perovskite nanocrystals.

[0017] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0018] The invention mixes 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, a photoinitiator and N,N-dimethylformamide, and performs polymerization reaction to obtain a P-AMDL polymer solution.

[0019] In the present invention, the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), methyl methacrylate (MMA), dimethylaminoethyl methacrylate (DMAEMA) and lauryl methacrylate (LMA) is preferably 1: (13-15): (0.5-0.7): (1.6-1.8), and more preferably 1: 14: 0.6: 1.7. In the present invention, the AMPS and DMAEMA contain polar groups, which can dissolve cesium halide and lead halide and anchor to the generated Cs x Pb y X z On the surface of nanocrystals, the lauryl group of LMA can provide hydrophobicity and dispersibility in toluene, thereby improving the Cs x Pb y X z The present invention controls the amount ratio of AMPS, MMA, DMAEMA and LMA within the above range, which can further improve the stability of Cs x Pb y X z Stability of nanocrystals.

[0020] In the present invention, the photoinitiator preferably includes diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO).

[0021] In the present invention, the molar ratio of the 2-acrylamide-2-methylpropanesulfonic acid to the photoinitiator is preferably 0.5:(0.06-0.07), and more preferably 0.5:0.07. The present invention controls the molar ratio of the 2-acrylamide-2-methylpropanesulfonic acid to the photoinitiator within the above range, so that the polymerization reaction can be fully carried out.

[0022] In the present invention, the volume ratio of the amount of 2-acrylamide-2-methylpropanesulfonic acid to N,N-dimethylformamide is preferably 0.5mmol:(2-4)mL. The present invention uses N,N-dimethylformamide as a solvent and controls its dosage so that the raw materials can be fully dissolved.

[0023] The present invention has no special limitation on the mixing operation of the 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, photoinitiator and N,N-dimethylformamide, and a mixing technical scheme well known to those skilled in the art can be used to ensure that the raw materials are mixed uniformly. In an embodiment of the present invention, the mixing is carried out under stirring at room temperature.

[0024] After the mixing is completed, the present invention preferably introduces argon gas into the mixed product for bubbling for 5 to 15 minutes before performing a polymerization reaction. The present invention uses argon gas to bubble, thereby removing oxygen from the mixed product, which is more conducive to the subsequent polymerization reaction.

[0025] In the present invention, the polymerization reaction is preferably carried out under ultraviolet light irradiation; the wavelength of the ultraviolet light is preferably 390-400 nm, more preferably 395 nm; the polymerization reaction time is preferably 3.5-4 h. The present invention controls the various parameters of the polymerization reaction within the above range, so that the polymerization reaction can be fully carried out.

[0026] After obtaining the P-AMDL polymer solution, the present invention mixes the P-AMDL polymer solution with cesium halide and lead halide to obtain a precursor solution.

[0027] In the present invention, the molar ratio of the cesium halide to the lead halide is 1:2 or 4:1. In the present invention, the halogen in the cesium halide and the lead halide is preferably one or both of chlorine and bromine.

[0028] In the present invention, when the molar ratio of cesium halide to lead halide is 1:2, a CsPb2X5 precursor is obtained, and subsequently CsPb2X5 nanocrystals are obtained.

[0029] In the present invention, when the molar ratio of cesium halide to lead halide is 4:1, a Cs4PbX6 precursor is obtained, and subsequently Cs4PbX6 nanocrystals are obtained.

[0030] In the present invention, the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to cesium halide is preferably 0.5:(0.1-0.4). The present invention controls the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to cesium halide within the above range, so that Cs x Pb y X z More polymers are anchored on the surface of nanocrystals to further increase the Cs x Pb y X z Stability of nanocrystals.

[0031] The present invention has no particular limitation on the mixing operation of the P-AMDL polymer solution with the cesium halide and the lead halide, and a mixing technical scheme well known to those skilled in the art is adopted to ensure that the lead halide and the cesium halide are completely dissolved and uniformly mixed. In an embodiment of the present invention, the mixing is carried out under stirring at room temperature.

[0032] After obtaining the precursor solution, the present invention mixes the precursor solution with toluene to perform double decomposition and coordination reactions to obtain a crude product.

[0033] In the present invention, the volume ratio of the precursor solution to toluene is preferably 1: (9-11), more preferably 1: 10. The present invention controls the volume ratio of the precursor solution to toluene within the above range, which is more conducive to obtaining regular crystals and improving Cs x Pb y X z Optical properties of nanocrystals.

[0034] In the present invention, the temperature of the double decomposition and coordination reaction is preferably 20-30°C; the time of the double decomposition and coordination reaction is preferably 10 min-4 h. In the present invention, during the double decomposition and coordination reaction, cesium halide and lead halide generate Cs x Pb y X z , polymer ligands anchored on Cs x Pb y X z surface, thus obtaining P-AMDL / Cs x Pb y X z Nanocrystalline crude product. The present invention controls the temperature and time of the double decomposition and coordination reaction within the above range, so that the reaction can be fully carried out.

[0035] After obtaining the crude product, the present invention mixes the crude product with n-hexane for precipitation to obtain cesium lead halide perovskite nanocrystals.

[0036] In the present invention, the volume ratio of the crude product to n-hexane is preferably 1: (0.8-1.2), more preferably 1: 1. The present invention uses n-hexane for purification, and controls its amount within the above range, which can avoid causing Cs x Pb y X z The nanocrystal structure is damaged, which improves the phase purity of the product.

[0037] In the present invention, the crude product is preferably mixed with n-hexane and then shaken before precipitation.

[0038] The present invention has no special limitation on the shaking operation, and any shaking technical solution well known to those skilled in the art may be adopted.

[0039] In the present invention, the precipitation time is preferably 5 to 15 minutes, more preferably 10 minutes; the precipitation is preferably carried out under static conditions.

[0040] After the precipitation is completed, the present invention preferably sequentially separates, washes and dries the precipitated product to obtain cesium lead halide perovskite nanocrystals.

[0041] The present invention has no special limitation on the operations of liquid separation, washing and drying, and the technical solutions well known to those skilled in the art can be adopted.

[0042] The preparation method of the present invention is simple, has a high Pb utilization rate, can be prepared in large quantities, and the feed ratio of cesium halide and lead halide meets the stoichiometric ratio, thereby eliminating the negative impact of excessive lead use and reducing the amount of toluene used, which is more conducive to actual production. In addition, by changing the molar ratio of cesium halide and lead halide, Cs with different dimensions can be obtained. x Pb y X z Nanocrystals.

[0043] In the present invention, the Cs x Pb y X z The nanocrystals preferably include Cs4PbBr6NCs, Cs4PbCl2Br4NCs, Cs4PbCl4Br2NCs, Cs4PbCl6NCs, CsPb2Br5NCs, CsPb2ClBr4NCs, CsPb2Cl4BrNCs or CsPb2Cl5NCs.

[0044] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1 A method for preparing Cs4PbBr6 nanocrystals: (1) weighing 0.50 mmol of AMPS, 7.01 mmol of MMA, 0.30 mmol of DMAEMA, 0.85 mmol of LMA and 0.07 mmol of TPO, adding them into 3 mL of DMF, stirring at room temperature until completely dissolved, bubbling argon for 10 min, and then irradiating under a 395 nm ultraviolet lamp for 4 h for polymerization to obtain a P-AMDL polymer solution; (2) Add 0.4 mmol of CsBr and 0.1 mmol of PbBr2 to the P-AMDL polymer solution and stir at room temperature until the solid is completely dissolved to obtain a Cs4PbBr6 precursor solution; (3) The precursor solution (200 μL) obtained in step (2) was quickly injected into 2 mL of toluene and reacted for 10 min to obtain a crude product of P-AMDL / Cs4PbBr6NCs; (4) Add 2.2 mL of n-hexane to the crude product obtained in step (3), shake it repeatedly for several times and let it stand for 10 min, discard the supernatant, and redisperse the bottom precipitate in 2 mL of toluene. Repeat the above steps three times for washing, and then dry it in a vacuum oven at room temperature to obtain Cs4PbBr6 nanocrystals with a Pb utilization rate of 35.6%.

[0046] Example 2 The PbBr2 in step (2) of Example 1 was replaced by PbCl2, and the other parameters were the same as those of Example 1, to obtain Cs4PbCl2Br4 nanocrystals with a Pb utilization rate of 29.8%.

[0047] Example 3 The CsBr in step (2) of Example 1 was replaced by CsCl, and the other parameters were the same as those of Example 1, to obtain Cs4PbCl4Br2 nanocrystals, with a Pb utilization rate of 28.9%.

[0048] Example 4 The CsBr in step (2) of Example 1 was replaced by CsCl, and PbBr2 was replaced by PbCl2. The other parameters were the same as those in Example 1, and Cs4PbCl6 nanocrystals were obtained. The Pb utilization rate was 29.5%.

[0049] Example 5 A method for preparing CsPb2Br5 nanocrystals: (1) weighing 0.50 mmol of AMPS, 7.01 mmol of MMA, 0.30 mmol of DMAEMA, 0.85 mmol of LMA and 0.07 mmol of TPO, adding them into 3 mL of DMF, stirring at room temperature until completely dissolved, bubbling with argon for 10 min, and then irradiating under a 395 nm ultraviolet lamp for 4 h for polymerization reaction to obtain a P-AMDL polymer solution; (2) Add 0.1 mmol of CsBr and 0.2 mmol of PbBr2 to the P-AMDL polymer solution and stir at room temperature until the solid is completely dissolved to obtain a CsPb2Br5 precursor solution; (3) The precursor solution (200 μL) obtained in step (2) was quickly injected into 2 mL of toluene and reacted for 4 h to obtain a crude product of P-AMDL / CsPb2Br5NCs; (4) Add 2.2 mL of n-hexane to the crude product obtained in step (3), shake repeatedly several times and let it stand for 10 min, discard the supernatant, and redisperse the bottom precipitate in 10 mL of toluene. Repeat the above steps three times for washing, and then dry it in a vacuum oven at room temperature to obtain CsPb2Br5 nanocrystals with a Pb utilization rate of 47.4%.

[0050] Example 6 The CsBr in step (2) of Example 5 was replaced by CsCl, and the other parameters were the same as those of Example 5, to obtain CsPb2ClBr4 nanocrystals with a Pb utilization rate of 41.2%.

[0051] Example 7 The PbBr2 in step (2) of Example 5 was replaced by PbCl2, and the other parameters were the same as those of Example 5, to obtain CsPb2Cl4Br nanocrystals with a Pb utilization rate of 65.3%.

[0052] Example 8 The CsBr in step (2) of Example 5 was replaced by CsCl, and PbBr2 was replaced by PbCl2. The other parameters were the same as those in Example 5, and CsPb2Cl5 nanocrystals were obtained. The Pb utilization rate was 53.0%.

[0053] The infrared spectra of AMPS, MMA, DMAEMA, LMA and P-AMDL in Example 1 are as follows: Figure 1 shown.

[0054] The nuclear magnetic resonance proton spectra of AMPS, MMA, DMAEMA, LMA and P-AMDL in Example 1 are as follows: Figure 2 shown.

[0055] The XRD patterns of the nanocrystals prepared in Examples 1 to 4 are as follows: Figure 3 As shown in the UV absorption spectrum Figure 4 shown.

[0056] The XRD patterns of the nanocrystals prepared in Examples 5 to 8 are as follows: Figure 5 As shown in the UV absorption spectrum Figure 6 shown.

[0057] The Cs4PbBr6 nanocrystals prepared in Example 1 were all dispersed in 2 mL of toluene to form a colloidal solution. The TEM image of the obtained colloidal solution is as follows: Figure 7 shown.

[0058] The CsPb2Br5 nanocrystals prepared in Example 5 were all dispersed in 10 mL of toluene to form a colloidal solution. The TEM image of the obtained colloidal solution is as follows: Figure 8 shown.

[0059] The thermal stability and UV stability of the CsPb2Br5 nanocrystals prepared in Example 5 are as follows Fig. 9 shown.

[0060] from Figures 1 to 8 It can be seen that the crystal structure and optical properties of the product of the present invention conform to the standard spectrum and have high phase purity.

[0061] from Fig. 9 It can be seen that the crystal structure of CsPb2Br5 nanocrystals remains unchanged after being heated at 200℃ and irradiated with UV for 10 h, respectively, and it has excellent thermal stability and UV stability.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing cesium lead halide perovskite nanocrystals, characterized in that: The following steps are involved: (1) 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate, lauryl methacrylate, a photoinitiator and N,N-dimethylformamide are mixed to carry out a polymerization reaction to obtain a P-AMDL polymer solution; (2) mixing the P-AMDL polymer solution obtained in step (1) with cesium halide and lead halide to obtain a precursor solution; the molar ratio of the cesium halide to the lead halide is 1:2 or 4:1; (3) mixing the precursor solution obtained in step (2) with toluene, performing double decomposition and coordination reaction, and obtaining a crude product; (4) The crude product obtained in step (3) is mixed with n-hexane for precipitation to obtain cesium lead halide perovskite nanocrystals.

2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid, methyl methacrylate, dimethylaminoethyl methacrylate and lauryl methacrylate is 1: (13-15): (0.5-0.7): (1.6-1.8).

3. The preparation method according to claim 1, characterized in that: The photoinitiator in step (1) includes diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide.

4. The preparation method according to claim 3, characterized in that: In the step (1), the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to the photoinitiator is 0.5:(0.06-0.07).

5. The preparation method according to claim 1, characterized in that: In the step (1), the volume ratio of the amount of 2-acrylamide-2-methylpropanesulfonic acid to N,N-dimethylformamide is 0.5 mmol: (2-4) mL.

6. The preparation method according to claim 1, characterized in that: The polymerization reaction in step (1) is carried out under ultraviolet light irradiation; the wavelength of the ultraviolet light is 390-400 nm; and the polymerization reaction time is 3.5-4 h.

7. The preparation method according to claim 1, characterized in that: The molar ratio of the 2-acrylamide-2-methylpropanesulfonic acid in step (1) to the cesium halide in step (2) is 0.5:(0.1-0.4).

8. The preparation method according to claim 1, characterized in that: In the step (3), the volume ratio of the precursor solution to toluene is 1:(9-11).

9. The preparation method according to claim 1 or 8, characterized in that: The temperature of the double decomposition and coordination reaction in the step (3) is 20-30° C., and the time of the double decomposition and coordination reaction is 10 min-4 h.

10. The preparation method according to claim 1, characterized in that: In the step (4), the volume ratio of the crude product to n-hexane is 1:(0.8-1.2).

Citation Information

Patent Citations

  • Preparation method of photoelectric material CsPb2Br5

    CN105948107A

  • Perovskite-like material CsPb2Br5, as well as synthetic method and application thereof

    CN107416894A

  • Large-size ultrathin all-inorganic lead halide perovskite nanosheet as well as preparation method and application thereof

    CN113620339A